2021
DOI: 10.1186/s40317-020-00225-9
|View full text |Cite
|
Sign up to set email alerts
|

Technologies for the automated collection of heat stress data in sheep

Abstract: The automated collection of phenotypic measurements in livestock is becoming increasingly important to both researchers and farmers. The capacity to non-invasively collect real-time data, provides the opportunity to better understand livestock behaviour and physiology and improve animal management decisions. Current climate models project that temperatures will increase across the world, influencing both local and global agriculture. Sheep that are exposed to high ambient temperatures experience heat stress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 112 publications
0
15
0
Order By: Relevance
“…Temperature and humidity index (THI) is the simplest approach, which combines ambient temperature and relative humidity to assess the response of livestock productivity as a function of climate [ 7 ]. As temperature and humidity are often readily collected, the minimal inputs make THI an easy tool for retrospective studies in most regions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Temperature and humidity index (THI) is the simplest approach, which combines ambient temperature and relative humidity to assess the response of livestock productivity as a function of climate [ 7 ]. As temperature and humidity are often readily collected, the minimal inputs make THI an easy tool for retrospective studies in most regions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tympanic temperature is susceptible to minor variations in AT due to being close to the hypothalamus. Animals under farm 1 management, with TT close or higher than 38.9 °C, could reduce their productivity, possibly by heat stress cases in its early stages (Baida et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that juveniles or adult males might respond differently to this stressor, although previous studies with similarly sized primates have not found substantial differences based on sex alone (Henzi et al, 2017. However, larger studies with a greater number of known individuals across a longer period might better address this question. Future research using arboreal camera traps or GPS collars with temperature probes might also be better able to address individualized questions (Lewis Baida et al, 2021).…”
Section: Climate and Resource Availabilitymentioning
confidence: 99%